Solid-phase Mn speciation in suspended particles along meltwater-influenced fjords of West Greenland. (1st June 2022) - van Genuchten, C.M.; Hopwood, M.J.; Liu, T.; Krause, J.; Achterberg, E.P.; Rosing, M.T.; Meire, L.
Abstract: Manganese (Mn) is an essential micro-nutrient that can limit or, along with iron (Fe), co-limit phytoplankton growth in the ocean. Glacier meltwater is thought to be a key source of trace metals to high latitude coastal systems, but little is known about the nature of Mn delivered to glacially-influenced fjords and adjacent coastal waters. In this work, we combine in-situ dissolved Mn (dMn) measurements of surface waters with Mn K-edge X-ray absorption spectroscopy (XAS) data of suspended particles in four fjords of West Greenland. Data were collected from transects of up to 100 km in fjords with different underlying bedrock geology from 64 to 70°N. We found that dMn concentrations generally decreased conservatively with increasing salinity (from 80 to 120 nM at salinity < 8 to < 40 nM at salinities > 25). Dissolved Fe (dFe) trends in these fjords similarly declined with increasing distance from glacier outflows (declining from > 20 nM to < 8 nM). However, the dMn/dFe ratio increased rapidly likely due to the greater stability of dMn at intermediate salinities (i.e. 10–20) compared to rapid precipitation of dFe across the salinity gradient. The XAS data indicated a widespread presence of Mn(II)-rich suspended particles near fjord surfaces, with structures akin to Mn(II)-bearing phyllosilicates. However, a distinct increase in Mn oxidation state with depth and the predominance of birnessite-like Mn(IV) oxides was observed for suspended particles in a fjord with tertiary basalt geology. The similar dMn behaviour in fjords with different suspended particle Mn speciation (i.e., Mn(II)-bearing phyllosilicates and Mn(IV)-rich birnessite) is consistent with the decoupling of dissolved and particulate Mn and suggests that dMn concentrations on the scale of these fjords are controlled primarily by dilution of a freshwater dMn source rather than exchange between dissolved and particle phases. This work provides new insights into the Mn cycle in high latitude coastal waters, where small changes in the relative availabilities of dMn, dFe and macronutrients may affect the identity of the nutrient(s) proximally limiting primary production.